2003
DOI: 10.1093/fampra/cmg518
|View full text |Cite
|
Sign up to set email alerts
|

How to use participatory action research in primary care

Abstract: PAR is very applicable in primary care. The principles of PAR such as mutual collaboration, reciprocal respect, co-learning and acting on results from the enquiry are essential in the doctor-patient relationship. Self-awareness, the ability to self-critique and reflect in a deep manner using such tools as a reflective diary are essential for nurturing the development of effective primary health care workers and consequently care structures for the patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The term community-based participatory research has been used to describe research conducted collaboratively with and within communities, in which the goals are improved community-based outcomes, and all phases of the project are approved by a committee that includes stakeholders and methodologists. [59][60][61][62][63][64] The principles of this research approach can be found in a position paper endorsed by the North American Primary Care Research Group. 65 The key features are a strong foundation of understanding, respect, and trust among the participating entities; a set of mutually agreed-upon goals; and a governance structure and rules of conduct that ensure that the process will remain collaborative from goal generation to implementation and dissemination of results.…”
Section: Participatory Research In Pbrnsmentioning
confidence: 99%
“…The term community-based participatory research has been used to describe research conducted collaboratively with and within communities, in which the goals are improved community-based outcomes, and all phases of the project are approved by a committee that includes stakeholders and methodologists. [59][60][61][62][63][64] The principles of this research approach can be found in a position paper endorsed by the North American Primary Care Research Group. 65 The key features are a strong foundation of understanding, respect, and trust among the participating entities; a set of mutually agreed-upon goals; and a governance structure and rules of conduct that ensure that the process will remain collaborative from goal generation to implementation and dissemination of results.…”
Section: Participatory Research In Pbrnsmentioning
confidence: 99%
“…Through participation in the research process, disempowered participants are expected to lose their fear, and shame, gain self-confidence, self-esteem and control, and develop an understanding of their own value. PAR is highly relevant for work with oppressed and disempowered communities with self-help groups and for health education [16,19,20]. The researchers become essentially facilitators or catalysts, and participants become co-learners in PAR; nobody is considered the expert [20].…”
Section: Introductionmentioning
confidence: 99%
“…PAR is highly relevant for work with oppressed and disempowered communities with self-help groups and for health education [16,19,20]. The researchers become essentially facilitators or catalysts, and participants become co-learners in PAR; nobody is considered the expert [20]. Insiders and outsiders work together as equals to solve problems.…”
Section: Introductionmentioning
confidence: 99%
“…Abstracts were scanned for indications of recording by local participants, and where this was found, the full article was scanned. Eight articles (Adjei-Nsiah et al, 2004;Ahari, Habibzadeh, Yousefi, Amani, & Abdi, 2012;Buchy & Ahmed, 2007;Faure, Hocde´, & Chia, 2010;Freudenthal et al, 2006;Gutberlet, 2008;Marincowitz, 2003;Schoepf, 1993) were retained and reviewed.…”
Section: Methodsmentioning
confidence: 99%